Performance and change process in organization ABC - Chen, Yen Jiin (2016)
The object of this study is Organization ABC in the retail industry. This organization has been having a good performance for the past 40 years with aggressive changes in organization structure and strategic management. However, the performance recently has dropped drastically. This study will focus on what and why this negative trend is happening to this organization. It will look into the internal and external issues such as current market trend, market economy situation, market competition and international competitors who have increased their treat, challenges and competitiveness in same business. One of the questions is about how does the organization change when the company is facing problems? Another is about whether the change process is right and appropriate? Furthermore, what is the outcome after the change? In fact, when an organization is willing to change which is a good move, but if it does not use the right process and strategies of change, it will compound problems. The objective of this study is to determine what are the appropriate decisions and actions to be adopted to improve corporate performance is Organization ABC to remain competitive and profitable. Also, it will determine the internal and external issues affecting the actual practice of change implementation. The method used in this study consists of structured and semi-structured interview with 10 senior and junior managers on their views toward change. According to the results of my observation and interview, Organization ABC had previously good performance record and led the retailing industry, because it dared to change to perform better .However, it did not use the correct method to handle the change process well during the change period .This had caused issues in the internal structure and also dissatisfaction among employees. In conclusion, the right change management and change process are very important in any organization because they will affect its performance. Using the right methods and strategies can produce the target outcomes and result.